Avaliação do padrão do ciclo sono-vigília e a cognição em estudantes de medicina com diferentes esquemas de horários de aulas - Silva, Francisca Patricia da (2010)
The sleep patterns of students entering the university, is accompanied by many factors that can lead to changes in sleep habits, such as academic demands, new social opportunities, reduced parental care and irregular teaching schedules. The irregular pattern of sleep-wake cycle is usually accompanied by several daytime consequences, for example, reduced levels of motivation, performance, concentration, alertness and mood as well as increased fatigue and sleepiness.Thus, there are numerous reasons to support the fact that these students may suffer damage in their academic performance. The aim of this study was to evaluate the sleep-wake cycle (SWC) and cognition in medical students with different schemes teaching schedules. One group started classes at 08am, while the other started at 07am. We analyzed the data from 88 volunteers, 39 from each group. However, only those who participated in both stages of the study (n = 78) underwent cognitive testing. For subjective evaluation of the SWC was used questionnaires to check the quality of sleep, chronotype, daytime sleepiness and sleep habits. For objective evaluation was used actigraphy. For cognitive assessment was used the test MoCA (Montreal Cognitive Assessment). The results indicate that the group has class earlier had a greater irregularity of the SWC and a worse performance in cognitive testing. There was a difference between the schedules the week and weekend in the subjective variables, bedtime, wake up and sleep duration in both groups. The objective variables, time in bed showed difference between the schedules the week and weekend to the group started class at 08am and the variables bedtime, get up time, actual sleep time, time in bed and wake bouts in the class at 07am. In the cognitive test, there were differences between the groups in overall score and in the areas of executive function and memory recall. Thus, it is suggested that the class starting time may cause irregularity of the SWC and the irregularity may cause mild cognitive impairment. Moreover, cognitive testing MoCA was sensitive to detect differences among students, although the difference between the schedules is small